The development push of refugees: evidence from Tanzania. (24th April 2018) - Maystadt, Jean-François; Duranton, Gilles
Abstract: We exploit a 1991–2010 Tanzanian household panel to assess the effects of the temporary refugee inflows originating from Burundi (1993) and Rwanda (1994). We find that the refugee presence has had a persistent and positive impact on the welfare of the local population. We investigate the possible channels of transmission, underscoring the importance of a decrease in transport costs as a key driver of this persistent change in welfare. We interpret these findings as the ability of a temporary shock to induce a persistent shift in the equilibrium through subsequent investments rather than a switch to a new equilibrium in a multiple-equilibrium setting.